Raw lacquer-associated familial chronic myelomonocytic leukemia with multi-hit TET2 mutations - Zhang, Yang; Luo, Yujiao; Peng, Hongling; Yin, Yafei; Zhang, Guangsen (Frontiers in Oncology, 2025)
BackgroundTo explore the potential association between long-term exposure to raw lacquer and the development of chronic myelomonocytic leukemia (CMML).MethodsWe analyzed the clinical and hematological characteristics of an elderly couple with CMML. Whole-exome sequencing (WES) was performed to identify relevant gene variants, with a focus on TET2 mutation status.ResultsTwo unrelated CMML patients within the same family, both with over 40 years of raw lacquer exposure, developed CMML. WES revealed that both patients harbored multi-hit TET2 gene mutations and lacked ASXL1 mutations. Both demonstrated relative sensitivity to hydroxyurea or hypomethylating agent (HMA) therapy. Unaffected family members lacked significant raw lacquer exposure.ConclusionsLong-term exposure to raw lacquer may be associated with the onset of familial CMML. CMML patients with multi-hit TET2 mutations in the absence of ASXL1 mutations may have a favorable prognosis.